Vienna Institute of Psychology at interwar period - Benetka, Gerhard (Studia Psychologica: Theoria et praxis, 2009)
The following paper outlines some aspects of the history of academic psychology in Interwar Vienna. The founding of the Viennese Psychological Institute in 1922 is described within the context of the German educational reform movement and against the background of the political situation in Austria after World War I. Conducted by Karl and Charlotte Buhler the Institute was developed into an international centre of psychological research. During the interwar period the Viennese School made important contributions to many fields of psychological research: for example to general psychology, social psychology, and life span psychology. In the following account the main emphasis is put on child psychology. During the 1920s Charlotte Buhlers research paved the way to include psychology in the social democratic reforms of the educational system and of social services, especially of youth welfare. After the so-called Anschluss in 1938 the close relations between psychologists and municipal authorities ended up in the collaboration of psychologists with the Children Euthanasia Program during the Nazi-period.